The United Nations and regional security : (Lynne Rienner, 2004)
Events in Europe over the past decade or so have created a dynamic requiring significant conceptual and practical adjustments on the part of the the United Nations and a range of regional actors, including the EU, NATO, and the OSCE. This volume explores the resulting collaborative relationships in the context of peace operations in the Balkans, considering past efforts and developing specific suggestions for effective future interactions between the UN and its regional partners. The authors also consider the implications of efforts in Europe for the regionalization of peace and security operations in Asia, Africa, and Latin America.